The camera-animot: Speculations on Matteo Garrone’s Cinematic Gaze - Gilebbi, Matteo (Quaderni d'Italianistica)

(untitled) (Iter Press, 2025)
This essay analyzes three specific filming techniques employed by Matteo Garrone: camera obstruction in Gomorrah (2008), shallow depth of focus in First Love (2004), and non-human point of view (POV) in The Embalmer (2002). I argue that these uncommon camera framings and movements produce alternative, uncanny, more-than-human points of view that question the privilege, centrality, and independence of the human perspective. These techniques are also essential to understanding central themes in Garrone’s oeuvre, in particular the expressionist tension of his cinema that he employs to expose the co-relationality of any life experience.